An Approach for Zika Virus Inhibition Using Homology Structure of the Envelope Protein - Fernando, Sandun; Fernando, Teshan; Stefanik, Michal; Eyer, Ludek; Ruzek, Daniel (Molecular biotechnology, 2016)
To find an effective drug for Zika virus, it is important to understand how numerous proteins which are critical for the virus' structure and function interact with their counterparts. One approach to inhibiting the flavivirus is to deter its ability to bind onto glycoproteins; however, the crystal structures of envelope proteins of the ever-evolving viral strains that decipher glycosidic or drug-molecular interactions are not always available. To fill this gap, we are reporting a holistic, simulation-based approach to predict compounds that will inhibit ligand binding onto a structurally unresolved protein, in this case the Zika virus envelope protein (ZVEP), by developing a three-dimensional general structure and analyzing sites at which ligands and small drug-like molecules interact. By examining how glycan molecules and small-molecule probes interact with a freshly resolved ZVEP homology model, we report the susceptibility of ZVEP to inhibition via two small molecules, ZINC33683341 and ZINC49605556-by preferentially binding onto the primary receptor responsible for the virus' virulence. Antiviral activity was confirmed when ZINC33683341 was tested in cell culture. We anticipate the results to be a starting point for drug discovery targeting Zika virus and other emerging pathogens.
Keywords: Zika virus; Chlorocebus aethiops; Models, Molecular; proteiny virového obalu; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; Druggability; Computer Simulation; virus zika; Viral Load; Vero buňky; vazebná místa; zvířata; molekulární modely; Binding Sites; Viral Envelope Proteins; Structural Homology, Protein; Small Molecule Libraries; Cercopithecus aethiops; virová nálož; počítačová simulace; antivirové látky; Antiviral Agents; strukturní homologie proteinů; knihovny malých molekul; Homology model; Animals; Polysaccharides; polysacharidy; Zika Virus; Drug discovery; Vero Cells